A targeted graphene nanoplatform carrying histamine dihydrochloride for effective inhibition of leukemia-induced immunosuppression. Issue 7 (13th June 2018) - Cherukula, Kondareddy; Nurunnabi, Md.; Jeong, Yong Yeon; Lee, Yong-Kyu; Park, In-Kyu
Abstract: Despite the introduction of many efficient post-consolidation therapies for complete relapse in leukemia patients, many patients suffer from relapse. Reactive oxygen species (ROS) are considered an important parameter in the immunosuppression of acute myeloid leukemia, where they suppress the cytotoxic action of immune cells such as NK cells and T cells. This study demonstrates a way to achieve effective inhibition of immunosuppression by loading the drug histamine dihydrochloride (HDC) onto graphene quantum dots (GQDs) using hyaluronic acid as a targeting moiety for K-562 cells. The prepared GQD-based nanoplatform was stable and achieved high drug loading on the surface, which resulted in a sustained drug release profile over a period of time. Additionally, the drug-loaded graphene nanoplatform proved to be non-toxic at higher concentrations to K-562 cells and could be effectively taken up into cells due to the targeting moiety. In vitro ROS detection assays proved that the HDC loaded graphene nanoplatform could effectively inhibit ROS and thus prevent the immunosuppression caused by leukemic cells.